Isu-Isu Dalam Bulan Syaaban: Analisis Menurut Perspektif Fiqh Hadith: Issues in Syaaban Month: An Analysis from Fiqh al-Hadith Perspectives - Md. Ariffin, Mohd Farhan; Ahmad, Khadher`; Rosele, Muhammad Ikhlas; Abd Shukur, Mohd Izzat (Online Journal of Research in Islamic Studies, 2020)
In Islamic calendar, Sha’ban is one of the months which contain values ​​of glory and greatness among Muslims, both historically, advantages and addition to the worship. No less also brought upon various issues on virtue and religious worship implementation in it. Misunderstandings of Sha'ban hadith and the existence of weak and fake hadiths have greatly influenced its manifestations. Even by the month of Sha’ban every year, arguments will take place on virtual chat sites. Most notably, disputes involved groups of scholar who hold against each other's beliefs. On the other hand, they announce that Sha’ban has a lot of barakah, and even sometimes its seems to be more superior than Ramadan. On the other hand, they strictly forbade any ritual, so does legalize the culture of tafsiq and tabdi' to the opposition. Therefore, efforts to harmonize both sides are important in developing wasatiyyah attitude among community. As one of the medium, this article strives to resolve each issues based on past and contemporary theologian writings. The analysis is done on real issue and highlights the true understanding based of al-Quran and Sunnah. Among the issues are the contradiction between numbers of fasting in Sha'ban, the presence of weak and fabricated hadith, the night of Nisfu Sha’ban and Surar Syaaban. As a result of special guidance in welcoming Sha’ban, Muslims can perform pious duties without any doubt. It is hoped that study result can be benefited onto the conduct of worship in Sha’ban.